Air passenger rights in European Union under Regulation 261/2004 - Sērmūksle, Annija (Riga Graduate School of Law, 2018)
This research will focus on air passenger rights in European Union. The first section will consist of exploring main legislations with respect of air carrier liability, passenger rights and international carriage by air. Further there will be evaluation of Regulation 261/2004 as well as exploration of obligations and rights stated in it. As Court of Justice often has been asked to give their opinion to national courts with respect of implementation of Regulation 261/2004, an analysis of most important cases will be compiled. This analysis will reveal grey zones of the Regulation. Following this there will be an analysis of main areas of complaints. After that this research will focus on exploring bodies and mechanisms assisting and helping consumers in order to contact air carrier and receive entitled reimbursement.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Air passenger rights